Perancangan Alat Penanggulangan Dini Bencana Banjir Berbasis Inframerah Dengan Mikrokontroller Atmega16, Pompa Air, Dan Calling - Eri Riana (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2018)
At the time of the rainy season requires us to be vigilant with their floods. To minimize losses caused by floods then the need for a tool that can detect and automatically controlling the floods. In general, automatic flood detector designed using Atmega microcontroller 16. The flood is detected by sensors Infrared sensors will then be forwarded to the microcontroller. Then Atmega microcontroller 16 will activate the buzzer relay and sim800l. With its active form buzzer sounds indicate a flood, the relay will automatically turn on the pump to suck up the water, and sim800l will make calls (calling). Thus we can immediately safeguard themselves and other valuables